HEMOPHAGOCYTAL LYMPHOHISTIOCYTOSIS - M.A. Maschan; G.A. Novichkova ("Paediatrician" Publishers LLC, 2009)
Hemophagocytal lymphohistiocytosis is a rare and frequently fatal disorder of immune response regulation, based on defects of cell cytotoxicity and hyper production of pro inflammatory cytokines. This disease is devided to genetically determinate types of hemophagocytal lymphohistiocytosis and secondary hemophagocytal syndromes, associated to infections, malignant neoplasm, autoimmune disease and immunodeficiency. The article gives a brief description of pathogenesis, clinical symptoms, and methods of hemophagocytal lymphohistiocytosis treatment.Key words: hemophagocytal lymphohistiocytosis, immunosuppression, ciclosporin A, etoposide, dexamethasone.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(3):66-75)